Answer:
This is true.
Step-by-step explanation:
Step 1: see that √27 is the same as √3*3*3 and thus 3√3
Step 2: remove parenthesis so that 2(1-3√3) becomes 2 - 6√3
Step 3: observe that the equation now becomes 6√3 + 2 - 6√3 = 2
if you simplify any further, you are left with 0=0, which is true.
Comment if there is any step that requires more details...
Answer:
6
√
(
3
x
+
5
)
(
3
x
−
2
)
Step-by-step explanation:
Answer:
It is +2 or since (+2)*(+2 ) gives. If you think that it would be (-2) also then you are wrong because root of a positive rational number is always positive number.
Step-by-step explanation:
Let the square root of four be ‘k’.
Then we have
(4)^1/2=k
(Squaring both sides)
4=(k)^2
=>(k)^2–4=0
=>(k)^2-(2)^2=0
=>[k+2][k-2]=0 {since (a)^2-(b)^2=(a+b)(a-b)}
if product of two numbers is 0 then either of one must be zero.
If k+2=0 then k=-2
If k-2=0 then k=2
From here we got two answers but -2 should be omitted because when we square an equation we add “root extra”which means that when we square an equation one root is added.
Answer:
Giving one KG equals 2.20 pounds how many kilograms are in 338 poun
Step-by-step explanation:
just simply fy it